2014
DOI: 10.1002/gps.4225
|View full text |Cite
|
Sign up to set email alerts
|

A review of amnestic MCI screening in east/southeast Asian older adults with low education: implications for early informant-clinician collaboration

Abstract: MCI misdiagnosis may be prevalent, highlighting the need for early collaborative work between informants and clinicians to improve the accuracy of this diagnosis in older Asian adults with low education. Findings were suggestive, although restricted in generalizability even within similar cultural groups or neighboring regions. Clinical application is limited, but some findings provide guidance for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Cognitive tests such as the MMSE and RAVLT are known to be biased regarding low education. 29 However, as our indices of cognitive resilience depended also on the degree of Aβ deposition, the results reported herein cannot be taken to simply reflect disease-independent relationships between CR proxies and current cognitive performance. Moreover, the association between CR and cognitive resilience remained significant in our sample when an RES index based on a larger cognitive composite comprising several neuropsychological task items was employed.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Cognitive tests such as the MMSE and RAVLT are known to be biased regarding low education. 29 However, as our indices of cognitive resilience depended also on the degree of Aβ deposition, the results reported herein cannot be taken to simply reflect disease-independent relationships between CR proxies and current cognitive performance. Moreover, the association between CR and cognitive resilience remained significant in our sample when an RES index based on a larger cognitive composite comprising several neuropsychological task items was employed.…”
Section: Discussionmentioning
confidence: 77%
“…The second prediction of our study was also confirmed, that is, that lower CR would be a significant predictor of reduced cognitive resilience to AD pathology. Cognitive tests such as the MMSE and RAVLT are known to be biased regarding low education 29 . However, as our indices of cognitive resilience depended also on the degree of Aβ deposition, the results reported herein cannot be taken to simply reflect disease‐independent relationships between CR proxies and current cognitive performance.…”
Section: Discussionmentioning
confidence: 87%
“…IR is an independent risk factor for MCI, and in the brain, may be associated with sporadic Alzheimer's disease [10,11]. Dementia prevalence is increasing with rapid aging in the population, and MCI as an intervention stage to prevent dementia has become a research hotspot [12,13]. Most recent studies have focused on the role of IR as possible links between diabetes and AD, and the disturbances in brain insulin signaling mechanisms may contribute to the molecular, biochemical, and histopathological lesions in AD [1,14].…”
Section: Introductionmentioning
confidence: 99%
“…Reviews (e.g. [96]) recommend using a combination of screening and informant information, with an emphasis on reports from a person who knows the patient well, comparing the person's present and past performance.…”
Section: The Issue Of Low Literacy Education and Culturementioning
confidence: 99%